Proust’s Innovative Vision of Literature as Seen Through his Correspondence - Pascal Ifri (Studies in 20th & 21st Century Literature, 2012)
Marcel Proust’s monumental correspondence is filled with information about the man Marcel Proust and his daily life, but reveals very little about his ideas on art and literature or about the novel that consumed his life, A la recherche du temps perdu. Most of his letters paint an extremely polite and even obsequious man overly concerned with pleasing his correspondents or with organizing his social life while others provide information about his personal life. When he mentions his writing, it is usually in connection with practical questions or information he is seeking. Very rarely does he discuss his novel or present his own ideas about art and literature. However, a handful of letters, out of thousands, in which he does discuss his literary project and his innovative vision of literature in some detail, show some sort of Proustian aesthetics that not only complements the theories he offers in Contre Sainte-Beuve and in Le Temps retrouvé, the last volume of his novel, but also helps understand them better.
Keywords: Proust; Marcel Proust; A la recherche du temps perdu; novel; letters; Proustian aesthetics; everyday life; Contre Sainte-Beuve; Le Temps retrouvé